2020
DOI: 10.1093/mnras/staa1137
|View full text |Cite
|
Sign up to set email alerts
|

K2 Ultracool Dwarfs Survey – VI. White light superflares observed on an L5 dwarf and flare rates of L dwarfs

Abstract: $Kepler\, K2$ long cadence data are used to study white light flares in a sample of 45 L dwarfs. We identified 11 flares on 9 L dwarfs with equivalent durations of (1.3–198) h and total (UV/optical/IR) energies of ≥0.9 × 1032 erg. Two superflares with energies of >1033 erg were detected on an L5 dwarf (VVV BD001): this is the coolest object so far on which flares have been identified. The larger superflare on this L5 dwarf has an energy of 4.6 × 1034 erg and an amplitude of >300 times the photosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…The differentiation seen as a function of mass is not inconsistent with the similar flare properties seen across a large range of stellar masses (e.g. De Luca et al 2020;Paudel et al 2020). Rather, higher-energy flares occur more frequently on more massive M-dwarfs prior to spindown (e.g.…”
Section: Flare Energetics and Morphology Predict Temperaturesupporting
confidence: 49%
“…The differentiation seen as a function of mass is not inconsistent with the similar flare properties seen across a large range of stellar masses (e.g. De Luca et al 2020;Paudel et al 2020). Rather, higher-energy flares occur more frequently on more massive M-dwarfs prior to spindown (e.g.…”
Section: Flare Energetics and Morphology Predict Temperaturesupporting
confidence: 49%
“…For low-mass main sequence stars, spectral classes K and M, flare stars are common, also powered by magnetic reconnection. Superflares (as greatly more energetic than normal flares) also occur on ordinary very-low mass main sequence stars, for example on Proxima Centauri (Howard et al 2018), L-type dwarfs (Paudel et al 2020), plus two late-M stars with Superflare amplitudes 9.5-16 mag (Schaefer 1990). For G-type main sequence stars, Superflares are seen with energies up to 2×10 38 ergs in field stars (Schaefer et al 2000), and are very-well observed on many solarlike stars inside the Kelper field (Maehara et al 2012).…”
Section: The Nature Of the Superflaresmentioning
confidence: 99%
“…To estimate the false discovery rate (FDR), some studies (Kowalski et al 2009;Osten et al 2012;Paudel et al 2018Paudel et al , 2020 have applied the FDR analysis following Miller et al (2001). However, the Miller's method is not applied to our project, because it requires a large number of null samples manually selected from the dataset of light curves, but this work cannot be finished automatically in real time by our pipeline.…”
Section: Flare Searchmentioning
confidence: 99%